Mechanistic Aspects of Reduction of tris(Pyridine-2-carboxylato) Manganese(III) by S2O32- in Na(pic)-picH Buffer - K. Sen Gupta, Kalyan; Bhattacharjee, Nandini; Pal, Biswajit (Asian Journal of Chemistry, 2015)
The oxidation of thiosulfate ion by tris(pyridine-2-carboxylato) manganese(III) in picolinate-picolinic acid buffer occurs according to the equation 2S2O32- + 2MnIII ® S4O62- + 2MnII. The reaction was studied under pseudo-first order conditions. The rate of the reaction is first order with respect to [S2O32-] and [MnIII] with no evidence of 1:1 complex formation between the reactants. The influence of pH on the reaction rate is insignificant. The rate of the reaction decreases with the increase in acrylamide concentration. The influence of temperature was studied in the temperature range 288-303 K. The values of DH¹ and DS¹ have been calculated to be 33 ± 2 kJ mol-1 and -137 ± 7 J K-1 mol-1, respectively. A one-equivalent electron transfer from S2O32- to MnIII takes place to give MnII and free radical, the latter subsequently is transformed to S4O62-. An attempt has been made to compare the results of the oxidation of some other sulfur, phosphorous and nitrogen containing inorganic compounds by this oxidant.